Simulation of the In Situ Spatially Varying Ground Motions and Nonlinear Seismic Response Analysis of the Cable-Stayed Bridge - Jin Zhang; Ke-jian Chen; Neng-pan Ju; Shi-xiong Zheng; Hong-yu Jia; Da-ping Yuan (Shock and Vibration)
To study the nonlinear seismic behavior and seismic resistance of the long-span cable-stayed bridges subjected to earthquakes, the multidimensional and multisupported artificial ground motions are synthesized first based on the in situ site conditions of the bridge considering the coherent and traveling wave effects. Then, considering the material nonlinearity of the cable-stayed bridge, a 3D finite element model is established based on the OpenSees platform, and the nonlinear seismic response analysis of the bridge is carried out under the synthetic artificial ground motions. The nonlinear seismic response of main bridge components such as piers, towers, bearings, and cables is analyzed, and key conclusions and observations are drawn.